KEWENANGAN KOMISI PEMBERANTASAN KORUPSI DALAM PENCEGAHAN TINDAK PIDANA KORUPSI BERDASARKAN UNDANG-UNDANG NO 30 TAHUN 2002 TENTANG KOMISI PEMBERANTASAN KORUPSI - Muhammad Badri (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
Corruption at this time has caused damage in various aspects of community life, the nation and the state that the prevention and eradication of corruption needs to be done continuously and sustainably. The government is trying to build a national political commitment to eradicate corruption by issuing regulations and provisions of law through legislation, for example: in No.X MPR / MPR / 1998 and TAP MPRNo.XI / MPR / 1998, Law No. 28 of 1999 on State Implementation of Clean and free from corruption, law No.31 of 1999 on Eradication of Corruption, Presidential Decree No. 81 Year 1999 on the Establishment of the State Wealth Audit Commission, undnag-undnag No. 20 of 2001 on the Amendment Act 31 of 1999 and Act No. 30 of 2002 on the Corruption Eradication Commission, later socialization conducted Komis Pemberantsan related corruption anti-corruption program is done by providing a comprehensive explanation and a more 'grounded' about the things that are included in the category of acts of corruption, it will be very effective giving signs for society and form of monitoring the state and government agencies are still biased more optimized implementation.Keyword :  eradication, prevention, corruption